Appraising Genji : literary criticism and cultural anxiety in the age of the last samurai - Caddeau, Patrick W., 1965- (Book collections on Project MUSE., 2006)
"Considered by many to be the world's first novel, The Tale of Genji by Murasaki Shikibu is a masterpiece of narrative fiction rich in plot, character development, and compositional detail. The tale, written by a woman in service to Japan's imperial court in the early eleventh century, portrays a world of extraordinary romance, lyric beauty, and human vulnerability. Appraising Genji is the first work to bring the rich field of Genji reception to the attention of an English-language audience. Patrick W. Caddeau traces the tale's place in Japanese culture through diaries, critical treatises, newspaper accounts, cinematic adaptation, and modern stage productions."--BOOK JACKET.